Mechanochromism triggered fluorescent color switching among polymorphs of a natural fluorescence pigment - Li, Meiqi; Zhang, Qi; Wang, Jian-Rong; Mei, Xuefeng (Chemical communications (Cambridge, England), 2016)
A naturally occurring pigment emodin is reported here as an example to extend mechanochromic luminescent material systems. Three polymorphs, two hydrates and the amorphous state of emodin, are successfully synthesized. These solid forms exhibit significantly different fluorescence properties, which indicates its potential application in mechano-sensors and security papers. The solid-state study of emodin demonstrates the feasibility of building new MCL systems via controlling the solid-state transition of natural fluorescent dyes.